Enhancement of Digital Stereo Vision Images based on Histogram and Gamma Correction Strategy - Kadmin, Ahmad Fauzan (Iraqi Journal of Science, 2022)
Image contrast enhancement methods have been a topic of interest in digital image processing for various applications like satellite imaging, recognition, medical imaging, and stereo vision. This paper studies the technique for image enhancement utilizing Adaptive Histogram Equalization and Weighted Gamma Correction to cater radiometric condition and illumination variations of stereo image pairs. In the proposed method, the stereo pair images are segmented together with weighted distribution into sub-histograms supported with Histogram Equalization (HE) mapping or gamma correction and guided filtering. The experimental result shows the experimented techniques outperform compare with the original image in evaluation parameters of visual quality and image enhancement parameters via Entropy, MSE, and PSNR, etc. taken for performance analysis and validation.